2021
DOI: 10.1249/mss.0000000000002656
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Power Output with Accumulating Levels of Work Done Is a Key Determinant for Success in Professional Cycling

Abstract: Introduction: This study aimed to investigate if performance measures are related to success in professional cycling and to highlight the influence of prior work done on these performance measures and success. Methods: Power output data from 26 professional cyclists, in a total of 85 seasons, collected between 2012 and 2019, were analyzed. The cyclists were classified as "climber" or "sprinter" and into category 1 (CAT.1; ≥400 PCS points (successful)) and CAT.2 (<400 PCS points (less successful)), based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…This decrement is caused by a small, non-significant decrease in anaerobic power (ES: 0.3), ultimately increasing the relative aerobic contribution during sprints. These rather small changes in sprint power during prolonged cycling are supported by a recent study where professional, successful cyclists maintained sprint-ability with accumulating levels of work done, and to a greater extent than non-successful cyclists (van Erp et al, 2021b). Ultimately, our data indicate an almost complete recovery of anaerobic power between repeated sets of maximal 30s sprints, which contributes to maintenance of sprint-ability during prolonged cycling.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This decrement is caused by a small, non-significant decrease in anaerobic power (ES: 0.3), ultimately increasing the relative aerobic contribution during sprints. These rather small changes in sprint power during prolonged cycling are supported by a recent study where professional, successful cyclists maintained sprint-ability with accumulating levels of work done, and to a greater extent than non-successful cyclists (van Erp et al, 2021b). Ultimately, our data indicate an almost complete recovery of anaerobic power between repeated sets of maximal 30s sprints, which contributes to maintenance of sprint-ability during prolonged cycling.…”
Section: Discussionsupporting
confidence: 88%
“…Accordingly, elite cyclists need to develop both a high aerobic capacity and the ability to repeatedly use anaerobic energy reserves. Indeed, successful, professional cyclists seem able to maintain sprint-ability after prolonged cycling, and to a greater extent than non-successful cyclists (van Erp et al, 2021b ). However, the changes in aerobic and anaerobic contributions during repeated sprints and the evolvement hereof during prolonged cycling is yet to be determined in elite cyclists.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work (van Erp et al 2021b;Leo et al 2021b) has shown a reduction in MMP values as prior work increases. However, future research is needed to better understand the mechanisms which lead to alterations in the power-duration due to fatigue, especially the influence of the exercise intensity and if work in different exercise intensity domains induce the same degree of downward shift in the powerduration curve.…”
Section: Future Directionsmentioning
confidence: 99%
“…In previous work, we found that U23 and professional cyclists could not only be differentiated by age but also by anthropometric characteristics [18]. Research has also shown differences in perfor- mance capacity between U23 and professional cyclists, such as the ability to minimise the downward shift in the power-duration curve and maximal aerobic power [12,18,34,35]. Previous research by Sallet et al [38] showed that in a non-fatigued state professional cyclists presented improved gross mechanical efficiency compared to U23 cyclists (25.6 ± 2.6 % vs. 24.4 ± 2.0 %).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in previous literature [33] professional road cycling is a team sport where in a multistage setting, domestiques primarily work for GC to put them in the ideal position for the key mountain climbs. Previous research has shown that sustainable power output drops after a given amount of work [18,34] therefore having domestiques perform tasks may enable GC to This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
Section: Discussionmentioning
confidence: 99%